Comparison of treatment results of acute and late injuries of the lisfranc joint - Tarczyńska, Marta (Sociedade Brasileira de Ortopedia e Traumatologia Regional de São Paulo, 2013)
OBJECTIVE: A retrospective comparison of treatment difficulties and treatment outcomes in Lisfranc joint injuries with late and early diagnosis. METHODS: The study group consisted of 10 patients diagnosed and treated properly within six months to 20 years of the accident causing the injury (mean six years). The control group consisted of the same number of randomly selected patients with a similar type of injury treated immediately after the accident. Mean follow-up was 13 years in the study group and eight years in the control group. The analysis evaluated the causes of the delay and the foot function at the time of follow up, measured using the AOFAS Midfoot Scale and the Lublin Foot Functional Score. The scores of the patients were analyzed using the non-parametric Mann-Whitney U test and the non-parametric Wilcoxon test. RESULTS: The control group had statistically significantly better scores on both scales. CONCLUSION: The main cause of treatment delay was misdiagnosis by the primary care physician. Level of Evidence III, Retrospective Comparative Study.